(untitled) (Revista Contexto & Educação, 2020)
Data from a historical educational research allowed the comprehension of how public authorities, from 1909-1927, developed educational projects aiming to promote vocational teaching to unprivileged minors in Curitiba/Paraná. The period 1909-1927 was set because of the definition of the concept “minor” by the Police Statistics Office, as well as the construction in Curitiba of the Patronato Agrícola, the first professional correctional institution for minors. Records present in the journals from the city of Curitiba were examined as well as the regulation of the patronat. From the method’s point of view, considering the social control systems as parameter, and then allowing the minor to be examined with their subjectivities. Dialoguing with PERROT(1988), FOUCAULT(1977), BENJAMIN(1985), ARENDT(2016), THOMPSON(1987) and HAN(2019) allows us to examine what happened at that moment. The data collected lead us to understand situations of child insurgency, that externalize educational systems with their evaluative repertoires and their rigorous collection mechanisms. Opportune to perceive, within these behaviors taken as intolerable, the constitution of a critical intersection to the regulatory system. Through this gap created by these apprentices, it was possible to perceive a vocational teaching structure with authoritarian practices, causing a painful and exclusionary teaching. A contradictory configuration as it aggravated the vulnerability of these children.